Iterative EM receiver for space-time coded systems in MIMO frequency-selective fading channels with channel gain and order estimation. - So, D.K.C (IEEE Transactions on wireless communications)
An iterative receiver for a space-time trellis coded system in frequency-selective fading channel is proposed. It performs channel gain estimation and sequence detection by using the expectation-maximization (EM) algorithm. Channel order estimation is included in the receiver to avoid unnecessary trellis computations by using the conditional model order estimator (CME). In addition, three modifications to the original CME criterion are proposed to improve the estimation accuracy. Simulation results show that the proposed receiver has a slight degradation in frame error rate performance to the known channel maximum likelihood receiver. Moreover, it outperforms the conventional fixed long-tap length EM receiver with a lesser complexity. Furthermore, the proposed modifications to the CME criterion improve the channel order estimation accuracy, thus minimizing unnecessary computations.